Coordinated increase of γ-secretase reaction products in the plasma of some female Japanese sporadic Alzheimer's disease patients: quantitative analysis of p3-Alcα with a new ELISA system - Konno, Tomoko; Hata, Saori; Hamada, Yukiko; Horikoshi-Sakuraba, Yuko; Nakaya, Tadashi; Saito, Yuhki; Yamamoto, Tohru; Yamamoto, Takayuki; Maeda, Masahiro; Ikeuchi, Takeshi; Gandy, Sam; Akatsu, Hiroyasu; et al. (Molecular neurodegeneration, 2011)
Background Aggregatable amyloid β-peptide (Aβ) and non-aggregatable p3-Alcα are metabolic products of the γ-secretase cleavage of amyloid β-protein precursor (APP) and Alcadeinα (Alcα), respectively. Familial AD (FAD) -linked mutations in the presenilin 1 or 2 (PS1 or PS2) component of γ-secretase can cause alternative intramembranous processing of APP and Alcα, leading to a coordinated generation of variants of both Aβ and p3-Alcα. Variant Alcα peptides have been observed in the cerebrospinal fluid (CSF) of patients with mild cognitive impairment and sporadic Alzheimer's disease (AD). Since, like APP, Alcα is largely expressed in brain, one might predict that alternative processing of Alcα would be reflected in body fluids of some AD patients. These patients with misprocessing of multiple γ-secretase substrates might define an endophenotype of p3-Alcα, in whom AD is due either to dysfunction of γ-secretase or to a disorder of the clearance of hydrophobic peptides such as those derived from transmembrane domains. Results We developed a simple procedure for extraction of p3-Alcα from plasma and for analyzing this extract in a sensitive, p3-Alcα-specific sandwich enzyme-linked immunosorbent assay (ELISA) system. Plasma p3-Alcα levels and Aβ40 levels were examined in sporadic AD subjects from two independent Japanese cohorts. In some of these patients, levels of plasma p3-Alcα were significantly higher, and were accompanied by parallel changes in Aβ40 levels. This AD-related difference was more marked in female subjects, but this phenomenon was not observed in subjects with frontotemporal lobar degeneration (FTLD). Conclusion Reagents and procedures have been established that enable extraction of p3-Alcα from plasma and for quantification of plasma p3-Alcα levels by ELISA. Some populations of AD subjects apparently show increased levels of both p3-Alcα and Aβ40. Quantification of p3-Alcα level may be useful as a readily accessible biomarker for a population of sporadic AD patients in which disease pathogenesis is associated with either dysfunction of γ-secretase or with a disorder of the clearance of transmembrane domain-derived peptides.